Common paddy disease identifier - Joe Wee, Tan (2011)
Rice paddy is important to Malaysia in terms of economic, food supplement and even as a culture for some ethnic. Yet the paddy yield by Malaysia farmers has always been infected by the crops disease such as Blast and Brown Spots.LPP officers have to move a lot to help farmers in rural areas.Sometimes farmer that are rural are located far from help.The objective of the system (Common Paddy Disease Identifier) is to develop a mobile prototype system that can identify the disease found on the paddy plants.Extreme programming is use as an approach to develop the system. This is because it promotes rapid application development under constraint time.Image processing technique such as Otsu, Median Blur,Sharpen and Prosterise has been studied thoroughly to use it during required phases of image processing.The system develop could identified three different disease that are rice blast,rice sheath blight and brown spot disease.If the system would be able to develop it could help a lot of farmers where sometimes officers from LPP are located too far.Besides this it also can help promote understanding of plant disease for students who are interested.